The immortal Hulk. Vol. 8, The keeper of the door - Ewing, Al, 1977- (Marvel Worldwide, Inc., 2020)
"The Hulk's archenemy has set his sights on infiltrating the green behemoth's friend group in preparation to enact his nefarious, long-fomenting plans. But can the Leader push the immortal Hulk beyond his breaking point? Meanwhile, when Bruce Banner first came to Shadow Base, he was cut up into pieces and stored in jars - but he was only the second test subject. The first subject has just been freed"--Back cover.